2010
DOI: 10.1021/la1022714
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of a Phospholipid Monolayer with Gas-Phase Ozone at the Air−Water Interface: Measurement of Surface Excess and Surface Pressure in Real Time

Abstract: The reaction between gas-phase ozone and monolayers of the unsaturated lipid 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine, POPC, on aqueous solutions has been studied in real time using neutron reflection and surface pressure measurements. The reaction between ozone and lung surfactant, which contains POPC, leads to decreased pulmonary function, but little is known about the changes that occur to the interfacial material as a result of oxidation. The results reveal that the initial reaction of ozone with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 26 publications
1
57
0
Order By: Relevance
“…The reaction chamber was mounted on the sample stage, it was interfaced with the gas setup, and the trough was filled with 80 mL of ACMW. A given amount of solution was spread using a microlitre syringe in order to form the monolayer following the protocol used in other NR studies of atmospheric relevance Sebastiani et al, 2015;Skoda et al, 2017;King et al, 2009King et al, , 2010Thompson et al, 2010). The volume of solution spread was 24 µL for d 34 OA, 23 µL for d 14 POA, 32 µL for d 33 MO and 35 µL for d 35 SA.…”
Section: Neutron Reflectometry (Nr)mentioning
confidence: 99%
“…The reaction chamber was mounted on the sample stage, it was interfaced with the gas setup, and the trough was filled with 80 mL of ACMW. A given amount of solution was spread using a microlitre syringe in order to form the monolayer following the protocol used in other NR studies of atmospheric relevance Sebastiani et al, 2015;Skoda et al, 2017;King et al, 2009King et al, , 2010Thompson et al, 2010). The volume of solution spread was 24 µL for d 34 OA, 23 µL for d 14 POA, 32 µL for d 33 MO and 35 µL for d 35 SA.…”
Section: Neutron Reflectometry (Nr)mentioning
confidence: 99%
“…Since O 3 is chemically reactive gas, it preferentially induces oxidation of endogenous unsaturated lipids present in pulmonary surfactant. (114,115) It is assumed that the secondary ozonation products, such as lysophospholipids, aldehydes and epoxycholesterol, mediate various cellular responses induced by O 3 . (114,116,117) We recently found that O 3 exposure (6 h, 2 ppm) induced significantly less lung inflammation in Prx1 deficient mice compared to WT mice monitored after 24 h. In bronchoalveolar lavage fluids (BALF), infiltrated immune cell numbers and protein levels of proinflammatory cytokines were significantly less in Prx1 deficient mice compared to WT mice (Yanagisawa et al.…”
Section: Roles Of Prxs In Tissue Inflammationmentioning
confidence: 99%
“…These reactions may be important in the production of atmospheric SOA, so changes to their nature and kinetics could be important in their own right, however their key relevance comes in that they determine the lifetime and ageing of the monolayer and, thus, the extent to which the water droplet is affected by all the physical and chemical changes detailed above that are due to the presence of that monolayer. Most monolayer studies to date (e.g., [30][31][32][33]) have focused on the less reactive initiator of the atmospheric oxidation ozone (O 3 ) that is known to be unreactive towards saturated surfactants (e.g., [34]). However, saturated surfactants have recently been shown to be of particular atmospheric importance [35], therefore processes that can attack saturated organic compounds are of particular interest.…”
Section: Introductionmentioning
confidence: 99%